2017
DOI: 10.1111/cmi.12808
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii infection shifts dendritic cells into an amoeboid rapid migration mode encompassing podosome dissolution, secretion of TIMP-1, and reduced proteolysis of extracellular matrix

Abstract: Dendritic cells (DCs) infected by Toxoplasma gondii rapidly acquire a hypermigratory phenotype that promotes systemic parasite dissemination by a "Trojan horse" mechanism in mice. Recent paradigms of leukocyte migration have identified the amoeboid migration mode of DCs as particularly suited for rapid locomotion in extracellular matrix and tissues. Here, we have developed a microscopy-based high-throughput approach to assess motility and matrix degradation by Toxoplasma-challenged murine and human DCs. DCs ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(77 citation statements)
references
References 51 publications
3
71
0
1
Order By: Relevance
“…Our data show that VGCC-CaM-CaMkII-Ras signaling mediate migratory activation of DCs upstream of Erk. Previously, we showed that the onset of the hypermigratory phenotype in DCs depends on live intracellular parasites and the discharge of T. gondii secretory organelles, independently of TLR-MyD88 signaling or chemotaxis (Fuks et al, 2012; Lambert et al, 2006; Olafsson et al, 2018; Sangare et al, 2019; Weidner et al, 2013). However, TLR-MyD88 signaling and chemotactic stimuli can also activate Erk.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our data show that VGCC-CaM-CaMkII-Ras signaling mediate migratory activation of DCs upstream of Erk. Previously, we showed that the onset of the hypermigratory phenotype in DCs depends on live intracellular parasites and the discharge of T. gondii secretory organelles, independently of TLR-MyD88 signaling or chemotaxis (Fuks et al, 2012; Lambert et al, 2006; Olafsson et al, 2018; Sangare et al, 2019; Weidner et al, 2013). However, TLR-MyD88 signaling and chemotactic stimuli can also activate Erk.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, in T. gondii -infected macrophages, both TLR-MyD88-dependent and a strong component of TLR-MyD88-independent Erk activation has been described (Kim et al, 2006). However, T. gondii -induced hypermigration is fully maintained in MyD88-deficient DCs (Lambert et al, 2006; Olafsson et al, 2018). Similarly, hypermigration is independent of chemotactic stimuli (but can act synergistically with chemotaxis upon stimulation) (Fuks et al, 2012; Kanatani et al, 2015; Weidner et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations